Novel silver nanoparticle-based biomaterials for combating Klebsiella pneumoniae biofilms - Elashkar, Eslam; Alfaraj, Rihaf; El-Borady, Ola M.; Amer, Mahmoud M.; Algammal, Abdelazeem M.; El-Demerdash, Azza S. (Frontiers in Microbiology, 2025)
BackgroundKlebsiella pneumoniae is a significant nosocomial pathogen that has developed resistance to multiple antibiotics, often forming biofilms that enhance its virulence. This study investigated the efficacy of a novel nanoformulation, AgNPs@chitosan-NaF, in combating K. pneumoniae biofilms.MethodsAntimicrobial susceptibility testing was performed to assess the antibiotic resistance profile of K. pneumoniae isolates. The antibiofilm activity of AgNPs@chitosan-NaF was evaluated using crystal violet staining and scanning electron microscopy. The underlying mechanisms of action were investigated through gene expression analysis.ResultsThe majority of K. pneumoniae isolates exhibited high levels of multidrug resistance. AgNPs@chitosan-NaF demonstrated superior biofilm inhibition compared to AgNPs@chitosan, significantly reducing biofilm biomass and disrupting biofilm architecture at MICs ranging from 0.125 to 1 μg/mL. Mechanistic studies revealed that the nanoformulation downregulated the expression of key biofilm-associated genes, including treC, fimA, mrkA, and ecpA. While AgNPs@chitosan-NaF exhibited a concentration-dependent cytotoxic effect on both normal and cancer cell lines, minimal cytotoxicity was observed at concentrations below 31.25 μg/mL.ConclusionThis study highlights the synergistic effect of silver nanoparticles, chitosan, and sodium fluoride in combating K. pneumoniae biofilms. The nanoformulation, AgNPs@chitosan-NaF, emerges as a promising therapeutic strategy to address the challenge of multidrug-resistant bacterial infections.